Music lessons and academic self-concept in 12- to 14-year-old children. (June 2014) - Degé, Franziska; Wehrum, Sina; Stark, Rudolf; Schwarzer, Gudrun
Music lessons increase children's performance on cognitive ability tests and promote academic achievement. The association between academic achievement and music lessons remains reliable even when IQ is held constant, which indicates that the association is more than a cognitive transfer effect. The question therefore arises of whether music lessons are associated with other variables that are related to academic achievement. The present study investigated whether the number of music lessons was associated with a child's academic self-concept, which is related to academic achievement. The sample comprised 92 12- to 14-year-old children (45 girls) who varied in their musical background. Academic self-concept and IQ were measured. Parents also provided detailed demographic background information (including information concerning music education). A hierarchical multiple regression was used in which socioeconomic status (i.e., parents' education), gender, nonmusical out-of-school activities, grade, and IQ were entered on the first step, and months of music lessons were added on the second step. This multiple regression analysis revealed that music lessons contributed significantly to the prediction of academic self-concept scores and significantly improved the fit of the model. Our data indicated a significant positive association between music lessons and academic self-concept, even when we controlled for confounding variables. These results support the idea that music lessons are associated with a personality variable (academic self-concept) that is related to academic achievement. However, the direction of causation still needs to be investigated because the present study is only correlational.